2014
DOI: 10.1111/1469-0691.12365
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism-based molecular typing of M. leprae from multicase families of leprosy patients and their surroundings to understand the transmission of leprosy

Abstract: The exact mode of transmission of leprosy is not clearly understood; however, many studies have demonstrated active transmission of leprosy around a source case. Families of five active leprosy cases and their household contacts were chosen from a high endemic area in Purulia. Fifty-two soil samples were also collected from different areas of their houses. DNA was extracted from slit-skin smears (SSS) and soil samples and the Mycobacterium leprae-specific RLEP (129 bp) region was amplified using PCR. Molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…In our previous studies, we found a diversity of M. leprae at eight SNP loci from clinical isolates obtained from leprosy patients or from multicase families residing mainly in Delhi and Purulia (West Bengal) regions. It was observed that SNP subtype 1D was the most predominant in the Indian population, SNP subtype 2E was noted only from the East Delhi region and SNP type 2 subtype G was noted only from the nearby areas of the Hoogly district of West Bengal (Lavania et al, 2013, Turankar et al, 2014. In this present study we got similar observations for SNP subtypes.…”
Section: Discussionsupporting
confidence: 87%
“…In our previous studies, we found a diversity of M. leprae at eight SNP loci from clinical isolates obtained from leprosy patients or from multicase families residing mainly in Delhi and Purulia (West Bengal) regions. It was observed that SNP subtype 1D was the most predominant in the Indian population, SNP subtype 2E was noted only from the East Delhi region and SNP type 2 subtype G was noted only from the nearby areas of the Hoogly district of West Bengal (Lavania et al, 2013, Turankar et al, 2014. In this present study we got similar observations for SNP subtypes.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, the predominance of SNP type 4 in Ceará is directly related to the Western African slaves. Similar to previous studies conducted in an endemic village in India, we found a concordance between the SNP subtyping (subtype 4-N) of M. leprae from skin biopsies and those from water samples 9,28 .…”
Section: Tablesupporting
confidence: 89%
“…Through PCR amplification of M. leprae DNA, its presence has been detected in environmental samples such as soil(11, 12) and water(13) in areas inhabited by leprosy patients in Brazil and India. The viability of M. leprae was assessed by its multiplication in footpads of wild type mice and showed that M. leprae can remain alive in wet soil for 46 days(14).…”
Section: Introductionmentioning
confidence: 99%